Modern heroes, modern slaves. - Boti, Marie; Guy, Malcolm; Boti, Marie; Wees, Michael; Hamelin, Babalou (cMulti-Monde Productions in association with Canadian Broadcasting Corporation., 1997)
Depicts the plight of Filipino migrant workers, the social costs and how the government promotes the export of labor.